2016
DOI: 10.1371/journal.pone.0165925
|View full text |Cite
|
Sign up to set email alerts
|

A Chlorfenapyr Mixture Net Interceptor® G2 Shows High Efficacy and Wash Durability against Resistant Mosquitoes in West Africa

Abstract: BackgroundMalaria control through use of long-lasting insecticidal nets (LN) is threatened by the selection of anopheline mosquitoes strongly resistant to pyrethroid insecticides. To sustain future effectiveness it is essential to identify and evaluate novel insecticides suitable for nets. Mixtures of two insecticides with contrasting mode of action have the potential to kill resistant vectors and restore transmission control provided the formulation can withstand regular washing over the net’s life span.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
109
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 21 publications
14
109
1
Order By: Relevance
“…However, a recent study in an area of high oxidase-based pyrethroid resistance in Mozambique found complete loss of An. funestus susceptibility following exposure to permethrin or deltamethrin that was only moderately restored after pre-exposure to PBO [46] suggesting that other next-generation ITNs incorporating chlorfenapyr [47] or pyriproxyfen [48] might be needed in settings of high pyrethroid resistance. In Malawi, Centers for Disease Control and Prevention bottle bioassays indicated that An.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study in an area of high oxidase-based pyrethroid resistance in Mozambique found complete loss of An. funestus susceptibility following exposure to permethrin or deltamethrin that was only moderately restored after pre-exposure to PBO [46] suggesting that other next-generation ITNs incorporating chlorfenapyr [47] or pyriproxyfen [48] might be needed in settings of high pyrethroid resistance. In Malawi, Centers for Disease Control and Prevention bottle bioassays indicated that An.…”
Section: Discussionmentioning
confidence: 99%
“…Although LLIN may provide some protection against insecticide-resistant Anopheles mosquitoes, this may depend on the frequency and strength of the resistance [7][8][9]. To meet the resistance challenge and restore malaria vector control, new active ingredients are being developed and tested.…”
Section: Introductionmentioning
confidence: 99%
“…The next generation of LLINs and indoor residual sprays (another method of delivering insecticides) is currently being deployed in Africa 9 . Simultaneously, new insecticide-based methods such as insect-attractive targeted sugar baits are being tested 10 .…”
Section: Flaminia Catterucciamentioning
confidence: 99%